CODE SWITCHING USED IN THE ENGLISH TEACHING AND LEARNING PROCESS IN THE FACULTY OF TEACHER TRAINING AND EDUCATION AT SRIWIJAYA UNIVERSITY - LINGGA AGUSTINA SUGANDA; ZURAIDA ZURAIDA (Sriwijaya University Learning and Education International Conference, 2016)
This study investigated the act of code switching which refers to the use of two languages, English and Indonesian, as a medium of instruction used by the teachers in the context of teaching and learning English as one of the courses in the Faculty of Teacher Training and Education at Sriwijaya University. The subjects - the teachers and students who were dealing directly with the use of code switching in the process of teaching and learning – were observed, interviewed, and given a set of questionnaire. This study yields three important results. First, the teachers use code switching in order to have a better communication with their students during the teaching and learning process, especially to transfer the material or topic of discussion in class so that the students can understand the material or topic better. Second, three language aspects – pronunciation, vocabulary, and grammar – were involved in this code switching phenomenon. Finally, students had a positive perception on their teachers‟ use of code switching during the teaching and learning process.